Nilai-Nilai Budaya “Taneyan Lanjang” Menjadi Ruh Pengelolaan Keuangan Usaha Keluarga di Madura: Sebuah Studi Etnografi - Lukman Hakim; Achdiar Redy Setiawan; Robiatul Auliyah (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2021)
This study seeks to uncover the practices of financial management of family business activities carried out by UD. Avien.The purpose of this study is to determine the pattern of financial management and the meaning of the perpetrators about all of their business activities. This research is a qualitative research through ethnographic approach. The main spirit values of Taneyan Lanjang has given colour at all stages of business financial management. The results of the study illustrate how the values of the Taneyan Lanjang culture are able to be in harmony with the business of financial management, which can create the value of awareness, religiosity, and profit sharing within the framework of kinship.